Don't fall for it: a short history of financial scams - Carlson, Ben (John Wiley & Sons, Inc, 2020)
"Why does financial fraud persist? Why do rich people get taken advantage of in financial scams? Who are some of the most successful charlatans and hucksters of all-time and why were they so successful? What are the financial and business lessons we can learn from some of the biggest frauds in history? What are the conditions under which fraud tends to work best? What steps can people take to avoid being taken advantage of with their money? Why is it often harder to stay rich than to get rich? Each chapter in the book will profile different frauds, charlatans, hucksters or victims of scams. Following stories and anecdotes about how these frauds were carried out, there will be studies and lessons detailing what can be learned from these experiences and how they apply to business, money management, and investing"--